Palliative sedation in amyotrophic lateral sclerosis: results of a nationwide survey among neurologists and palliative care practitioners in Germany - Salzmann, Laura; Alt-Epping, Bernd; Simon, Alfred (BMC neurology, 2022)
Palliative sedation has become widely accepted as a method to alleviate refractory symptoms in terminally ill patients. Controversies regarding this topic especially concern the use of palliative sedation for psychological symptoms, the use in patients who are not imminently dying and the simultaneous withdrawal of life-sustaining measures. Amyotrophic lateral sclerosis (ALS) is characterized by symptoms including muscle weakness, dysphagia, dysarthria, muscle spasms and progressive respiratory insufficiency. Due to these characteristic symptoms, palliative sedation might be considered to be necessary to alleviate refractory suffering in ALS patients. However, palliative sedation in ALS is only rarely discussed in current medical literature and guidelines.